2015
DOI: 10.1071/ch14562
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterisation, and Spectroscopic Properties of Copper(I) Complexes and their Applications to Dye-Sensitised Solar Cells

Abstract: Based on the ligand 1,4-bis(2-(diphenylphophino)benzylideneamino)benzene (pbb), two complexes, [Cu 2 (pbb)(2,2 0bipyridine) 2 ](BF 4 ) 2 (1) and [Cu 2 (pbb)(phen) 2 ](BF 4 ) 2 (2), have been prepared and characterised by IR, 1 H NMR, 31 P NMR, 19 F NMR, and 11 B NMR spectroscopy and X-ray crystal structure analysis. Structural analysis reveals that complexes 1 and 2 contain 1D infinite chains and 2D supramolecular networks constructed by C-HÁÁÁp and pÁÁÁp interactions, and an ordered-layer-lattice of BF 4 À is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…In this context, two studies were reported in 2015 by the Huang group, using tetracoordinating ligands to access dinuclear copper complexes. In their first publication, the authors described the use of the PNNP 7 ligand in combination with two bipyridine ( NN 261 ) or phenanthroline ( NN 1 ) ligands to obtain two novel dinuclear complexes (entries 31 and 32 in Table ). Despite their ligands possessing no anchoring groups and no intense absorption band in the visible region, the authors attempted the sensitization of a TiO 2 electrode with their newly synthesized complexes, with poor success however.…”
Section: Applications Of Photoactive Copper Complexesmentioning
confidence: 99%
“…In this context, two studies were reported in 2015 by the Huang group, using tetracoordinating ligands to access dinuclear copper complexes. In their first publication, the authors described the use of the PNNP 7 ligand in combination with two bipyridine ( NN 261 ) or phenanthroline ( NN 1 ) ligands to obtain two novel dinuclear complexes (entries 31 and 32 in Table ). Despite their ligands possessing no anchoring groups and no intense absorption band in the visible region, the authors attempted the sensitization of a TiO 2 electrode with their newly synthesized complexes, with poor success however.…”
Section: Applications Of Photoactive Copper Complexesmentioning
confidence: 99%